MENGATASI SISWA TERLAMBAT DATANG KE SEKOLAH MELALUI PENDEKATAN BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT PADA SISWA SMA N 1 NALUMSARI - Oktafia, Rulyana Mutiara; Kusmanto, Agung Slamet; Hidayati, Richma (Universitas Muria Kudus, 2024)
The aims of this research are: 1. To determine the factors that cause being late to school, 2. Overcoming late arrival to school by using Self Management techniques for students at SMA N 1 Nalumsari. This research was carried out at SMA N 1 Nalumsari, the research method used was combined research (Mix Method). The data collection techniques used were observation, interviews and documentation. Respondents in this research were guidance and counseling teachers, homeroom teachers, fellow students, and students. The results of counselee I's research revealed that BP was a student in class XI-7. BP is one of the students who has the problem of often being late to school. According to some information collected by researchers, the problems experienced by BP are due to internal and external factors, namely internal factors because he always stays up late at night, external factors because of the influence of friends who make BP often late to school. school. Counselor II FZA is a student in class late for school.